Proximate composition, mineral content, cooking quality, and sensory properties of Kalinga mix and Moringa noodles - Lanorio, Ma. Cristina; Lalap, Belinda Ramores; Felix, Angelina; Gonzales, Pamela; Maneja, Ma. Charina; Castaneda, Ana; Abuyog, Arnold (Open Science Journal, 2022)
The main objective of this study is to develop an acceptable and nutrient-dense noodles from KALINGA mix and moringa. Materials for making the noodles such as KALINGA mix (rice, sesame seeds, mung bean), bread flour, and moringa powder were purchased at the local market of Los Baños, Laguna. Malnutrition in the Philippines remains to be a serious health problem, especially to low-income areas. Its challenges and enormity in the country require new research and innovations that are accessible and will make use of native resources to achieve better health and nutrition for the community. Hence an attempt to develop an acceptable and nutrient-dense noodles incorporating KALINGA mix and moringa. The noodles were prepared with different ratios of KALINGA mix (30g, 20g, 10g) and flour (70g, 80g, 90g, 100g). All samples were then added with 5g of moringa. The results of the study showed that all the cooking losses of the samples were below the technologically acceptable limit (≤8%). In the overall acceptability, the sample with 30g KALINGA has the highest mean score of 7.125 (like moderately). The proximate composition showed that the highest moisture content (7.64%), and crude protein (10.86%) were found in 10g KALINGA, whereas crude fat (15.57%), and ash (1.0%) were the highest in 30g KALINGA, crude fiber (0.73%) and NFE (69.77%) were highest in the control sample. For the mineral content, the control sample was highest in calcium (125 mg/100g), and iron (7.4mg/100g) while the 30g KALINGA had the lowest in both. Zinc is the same in all samples (1.2 mg/100g). In conclusion, the sample with 30g KALINGA was good in terms of its cooking quality, overall acceptability, and proximate composition. The control however was better in its calcium, and iron content. <!–[if !supportAnnotations]–> <!–[endif]–>